An evaluation of the collection of the Development Bank of the Philippines and Landbank libraries with implications for collection development - Bongco, Antonio Jose D.; Cabbab, Johann Frederick A. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1998)
The primary aim of this study is to evaluate the collection of the Development Bank of the Philippines and Landbank and to find out if these libraries meet the needs of its clientele. The study made use of the quantitative and qualitative methods. Instruments used were the questionnaires administered to the library users and an interview guide for the interviews conducted with the head librarians. Visits to these institutions made the researcher gather other information like the library's budget, growth rate, and expenditures. Problems encountered by these libraries were also included.
The researcher concludes that both libraries meet the needs of its users only on the subject areas they specialize in -- Business Management and Training & Development. Most of the books or materials in need were on subject matters other than their scope, example, science and technology, computers, communication, etc.
The Landbank library has difficulties in acquiring the books requested because of the tight budget and the tedious process the request will have to go through. The administration always has the final say on such requests. The DBP library, on the other hand, has no problems on acquiring requested materials because they have enough budget to cover these requests. The library personnel deliberately requests if they are worth acquiring or not. Aside from this, the DBP library has other schemes in meeting the needs of its users like referring them to other departments, or libraries, and in the Inter-Library loan in some special cases.
Computer print out.
Vita
Thesis (Bachelor of Library Science)--University of the Philippines Diliman
Keywords: Development Bank of the Philippines -- Library resources -- Evaluation; Liandbank Library -- Library resources -- Evaluation